Особенности отпускной хрупкости сварных соединений паропроводов - Дмитрик, Виталий Владимирович; Сыренко, Т. А. (НТУ "ХПИ", 2010)
Изучены особенности отпускной хрупкости металла сварных соединений паропроводов ТЭС, состоящих из теплоустойчивых перлитных сталей 15Х1М1Ф и 12Х1МФ, длительно эксплуатирующиеся в условиях ползучести. Установлено, что отпускную хрупкость обеспечивает неравновесная зернограничная сегрегация легирующих и примесных элементов.

Some peculiarties of the metal tempering brittleness in the weld joints of the thermal power plent’s steam conduits consisting of heat resistant pearlitic steels 15Х1М1Ф and 12Х1МФ prolonged running under creep conditions have been studied. It has been determined found that the tempering brittleness was provided by the disbalanced grain boundary segregation of the alloying and a dmixturing elements
The peculiarities of the downhole shortness of the steampipe’s welded joinsngs
Keywords: ТЭС; сварные соединения; теплоустойчивые перлитные стали; условия ползучести